Vitreoretinal surgery - Williamson, Thomas H. (Springer Berlin Heidelberg, 2013)
This is the second edition of a highly successful textbook that in many areas has become the preferred manual of vitreoretinal surgery. It provides a complete guide to all common vitreoretinal surgical procedures and also covers diagnosis and other aspects of management. Because it is a single-author publication, there is minimal duplication in the text, avoiding the confusion and overlap characteristic of multiauthor publications. The book is designed to allow a trainee or professional vitreoretinal surgeon to determine the best methodology in individual cases. In order to acquaint the reader with different opinions, "surgical pearls" have been contributed by other international experts in vitreoretinal surgery. These have been welcomed in the past as an illustration of alternative methods, without detracting from the overall method described by the main author. Vitreoretinal Surgery will continue to prove particularly popular amongst trainees, but will also be of value to practicing professionals who need help in the management of difficult and rare cases. The text is backed up by the provision of videos that illustrate some aspects of the surgery.